Interpreting the role of epigallocatechin-3-gallate in Epstein-Barr virus infection-mediated neuronal diseases - Rani, Annu; Saini, Vaishali; Njini, Nfor Gael; Dixit, Amit Kumar; Meena, Ajay Kumar; Jha, Hem Chandra (Folia microbiologica, 2025)
The increasing prevalence of neurodegenerative diseases is a formidable task due to their multifactorial causation and treatments limited to disease maintenance and progression. Epstein-Barr virus (EBV) is reported to be involved with neuropathologies; previous studies from our group suggested the effective binding of epigallocatechin-3-gallate (EGCG) with EBV nuclear antigen 1 (EBNA1) and glycoprotein H (gH). Therefore, in the current study, we evaluated the anti-EBV effect of ECGG on the neuronal cells. EBV-GFP exhibited a decline after EGCG treatment. We have observed a decrease in specific latent and lytic cycle genes. EBNA1 unravelled attenuation at day 1 (D1), whereas EBNA3B, EBNA3C, BMRF1, BZLF1, and gp350 showed major downregulation in D3 compared to EBV infection. Notably, EBNA-LP has shown mitigation in both the considered time points. Inflammatory and chemokine moieties like IL-6, CCR1, CCR3, and CCR5 declined upon EGCG treatment, while IL-10 exhibited elevation. Transcription factor STAT3 and NF-kB were decreased, especially in the pre-EGCG treated samples. Subsequently, restoration in the mitochondrial membrane potential was observed after EGCG treatment. We observed an increase in the mitochondrial fission genes like DRP1 and MiD49, and not many regulations were observed in the mitochondrial fusion genes except MFN2. Furthermore, the CytC, CytC oxidase, MAVS, ANT, and SDH exhibited elevation upon EGCG treatment, while ATPsyn and ABAD showed downregulation. Dysfunction of mitochondria is further related to apoptosis of neurons. Herein, we were keen to examine the level of amyloid-precursor protein (APP), and it has also indicated declined after EGCG treatment. Altogether, the current study demonstrated the anti-EBV effect of EGCG by subsiding the EBV-mediated inflammation and amendments in the neuropathological markers.
Keywords: Neuroinflammation; APP; Neurons; Epigallocatechin-3-gallate; Neurodegeneration; Epstein-Barr virus